Hypophosphatemia in very low birth weight infants receiving parenteral nutrition - Rowjee, Vikesh (My University, 2020)
Objective To retrospectively assess serum bone mineral (BM) biochemistry in preterm (PT) infants with a birth weight (BW) ≤1500g that had received at least 5 days of parenteral nutrition (PN). Study design- One hundred and nine patient files between July 2013 and June 2014 at Chris Hani Baragwanath Hospital (CHBAH) were assessed for volumes of nutritional support received, and BM biochemistry performed. Results Median gestational age was 29 weeks (IQR 28-30 weeks). Median BW was 1065g (IQR 935-1210g). Majority of the BM levels were obtained in weeks 3-5 of life. The median PO4 was 1.71mmol/L (IQR 1.43-1.92mmol/L). There was a negative correlation between PO4 and increasing volumes of PN (p = 0.005, r = -0.2416) and a positive correlation between PO4 and increasing volumes of formula feeds, (p = 0.042, r = 0.3153). Conclusion Preterm infants weighing ≤1500g requiring PN for ≥5 days are susceptible to developing hypophosphatemia.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Master of Medicine in the branch of Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020